FATIGUE OPTIMIZATION OF TRIANGLE TRACK WHEEL UNDER MULTI-WORKING CONDITIONS BASED ON ENSEMBLE OF SURROGATE MODEL - LI YongXin; CHANG Tao; YANG LiMing; LI KaiLun; SUN YinXu; WU FengHe (Jixie qiangdu)
Triangular track wheels of emergency rescue vehicles need high mobility and reliability under various terrain conditions. Aiming at overlong time of multi-working fatigue optimization calculation,ensemble of surrogate model is used to accelerate the optimization solution. In order to ensure convergence accuracy,a new evaluation index of surrogate model is proposed. First of all,fatigue life of support frame of replaceable triangular track wheel under four working conditions is analyzed.Then,based on Kriging model and response surface model,ensemble of surrogate model is constructed for mass and fatigue life.In order to approach global optimal point more easily,ensure same concavity and convexity between predicted value and observed value,local trend deviation is proposed as evaluation criterion of constructing ensemble model. Finally,size optimization of support frame is constructed. Results show ensemble of surrogate model not only ensures calculation accuracy,but also has robustness. Fatigue life of triangular track wheel after lightweight design is increased by 43. 59%.